If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-11 + b) = 16 (-11 * -1 + b * -1) = 16 (11 + -1b) = 16 Solving 11 + -1b = 16 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1b = 16 + -11 Combine like terms: 11 + -11 = 0 0 + -1b = 16 + -11 -1b = 16 + -11 Combine like terms: 16 + -11 = 5 -1b = 5 Divide each side by '-1'. b = -5 Simplifying b = -5
| 256(5)+3(11)= | | 5x-7=8x-58 | | 6+4=4 | | -3-7=-x-2 | | 5(-2+n)=35 | | Ix+2y=0 | | 5b-1=-31 | | 6(x+8)+3x=-2(x-2) | | Y-6=4(x-12) | | y=2x-x-7 | | 6(x+8)+3a=-2(x-2) | | 40+3x=73 | | 7x+2=-3+2x+25 | | 2*ln(x)-ln(4)=0 | | -40-6k=-3(-k+6)+5 | | (2x+10)=(120) | | 26x=180+24-35 | | 2x+2-4=7-2+4 | | A+2(a-5)=320 | | -8(x-1)=6x-6 | | 2.6(t+2)=(1.3t+2)+1.2 | | 4x+4x=90 | | 28-p=5(p-4) | | 2x+3-9=0 | | -6(x-8)=39-3x | | -x+3+12x=-4+4x+49 | | 5y^5-5y^4-10y^3=0 | | -8-5(m+3)=27+5m | | 4x+3=(x-6) | | 12X+26=19X+30 | | 4(p-3)=8(p+5) | | 5t^2+8t-30=0 |